2009
DOI: 10.1167/iovs.08-2981
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nectin-1, HVEM, and PILR-α in HSV-2 Entry into Human Retinal Pigment Epithelial Cells

Abstract: Purpose Herpes simplex virus-type 2 (HSV-2) can cause Acute Retinal Necrosis (ARN), which can lead to exudative and rhegmatogenous retinal detachment; yet, little is know about the cellular and molecular mechanisms of HSV-2 entry into retinal pigment epithelial (RPE) cells. The goal of this study was to establish the identity of the critical receptors utilized by the virus for infection. Methods A reporter HSV-2 virus, which expresses beta-galactosidase, was used to quantify entry into RPE cells and viral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…However, high affinity interactions (accompanied by conformation changes) may not be blocked by antibodies and therefore, the net effect by combining the antibodies may not be significantly higher than individual effects. This may be a reason why a near complete blocking of HSV-1 infection by antibodies has been extremely rare even when all gD receptors were blocked (Akhtar et al, 2008;Shukla et al 2009). Our results, nevertheless, highlight that syndecan-1 and syndecan-2 play a critical role during HSV-1 entry and that the two HSPGs show detectable differences in their abilities to facilitate infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, high affinity interactions (accompanied by conformation changes) may not be blocked by antibodies and therefore, the net effect by combining the antibodies may not be significantly higher than individual effects. This may be a reason why a near complete blocking of HSV-1 infection by antibodies has been extremely rare even when all gD receptors were blocked (Akhtar et al, 2008;Shukla et al 2009). Our results, nevertheless, highlight that syndecan-1 and syndecan-2 play a critical role during HSV-1 entry and that the two HSPGs show detectable differences in their abilities to facilitate infection.…”
Section: Discussionmentioning
confidence: 99%
“…Many known protein receptors for HSV-1 entry can be blocked by antibodies, which in turn, blocks viral entry (Akhtar et al, 2008;Shukla et al 2009). Similar to those receptors, we also found that pAbs against synedecan-1 and syndecan-2 block entry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many known protein receptors for HSV-1 entry can be blocked by antibodies, which in turn, blocks viral entry [157,169]. Similar to those receptors, we also found that pAbs against synedecan-1 and syndecan-2 block entry.…”
Section: Discussionsupporting
confidence: 75%
“…However, high affinity interactions (accompanied by conformation changes) may not be blocked by antibodies and therefore, the net effect by combining the antibodies may not be significantly higher than the individual effects. This may be a reason why a near complete blocking of HSV-1 infection by antibodies has been extremely rare even when all gD receptors were blocked [157,169]. Our results, nevertheless, highlight that syndecan-1 and syndecan-2 both play a critical role during HSV-1 entry and that the two HSPGs show detectable differences in their abilities to facilitate infection.…”
Section: Discussionmentioning
confidence: 66%